Pengaruh Literasi Keuangan, Perilaku Keuangan dan Financial Technology pada Keputusan Investasi - Chotimah, Chusnul; Afifudin, Afifudin; Nandiroh, Umi (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This study examines how financial literacy, financial behavior, and financial technology influence investment decisions among students at the Faculty of Economics and Business, Islamic University of Malang. Investment decisions are the dependent variable, while the other three factors are independent variables. Primary data is collected through surveys, and the research uses quantitative methods. The sample, selected using purposive sampling and calculated with the Slovin formula, includes 100 students. Various statistical techniques, including regression analysis, classical assumption tests, descriptive statistics, and hypothesis testing, are used to assess the hypotheses.Keywords: Financial literacy, financial behavior and financial technology investment